Aluminum induced intestinal dysfunction via mechanical, immune, chemical and biological barriers. (February 2022) - Hao, Wudi; Hao, Chenyu; Wu, Chengrong; Xu, Yuqing; Jin, Cuihong
Abstract: Aluminum is the most abundant metal element in the Earth's crust, which exists naturally in the form of aluminum compounds. Aluminum is mainly absorbed through the gastrointestinal tract, which varies with different aluminum compounds. During this process, aluminum could induce the disruption of intestinal mucosa barrier. However, its underlying mechanism has not been elucidated yet. Previous studies have reported that aluminum can firstly promote the apoptosis of intestinal epithelial cells, destroy the structure of tight-junction proteins, and increase the intestinal permeability, injuring the mechanical barrier of gut. Also, it can induce the activation of immune cells to secrete inflammatory factors, and trigger immune responses, interfering with immune barrier. Moreover, aluminum treatment can regulate intestinal composition and bio-enzyme activity, impairing the function of chemical barrier. In addition, aluminum accumulation can induce an imbalance of the intestinal flora, inhibit the growth of beneficial bacteria, and promote the proliferation of harmful bacteria, which ultimately disrupting biological barrier. Collectively, aluminum may do extensive damage to intestinal barrier function covering mechanical barrier, immune barrier, chemical barrier and biological barrier. Graphical abstract: Image 1 Highlights: Aluminum was mainly absorbed through gastrointestinal tract, which in turn induce intestinal dysfunction. The absorption of aluminum varies with different aluminum compounds. Aluminum disrupted the intestinal barrier system including mechanical, immune, chemical and biological barriers.